Compensation for Loss of Work Income in Personal Injury Cases - Leif Danziger; Eliakim Katz (Center for Economic Studies and ifo Institute (CESifo), 2017)
What is the appropriate lump-sum compensation for loss of work income in personal injury cases? Since generally future work income is not known with certainty, compensation for its loss must be based on statistical considerations. Typically, courts have based awards on mean or median work income, but apparently without meaningful grounding in economics. We use economic theory to address this issue. We find that the relation between the appropriate compensation and the mean and median work income depends on the uncertainties of work income and of consumption facilitated by the lump-sum compensation awarded, as well as the degree of risk aversion. Since the consumption uncertainty associated with compensation generally exceeds that associated with work income, we conclude that the lump-sum compensation should exceed mean and therefore median work income.
Keywords: K13; 330; law and economics; personal injury; income loss; compensation; uncertainty; risk aversion